The G20 macroeconomic agenda : India and the emerging economies - Shome, Parthasarathi, 1950- (Cambridge : Cambridge University Press, 2014)
As the premier forum for global economic governance, G20 was successful in warding off the global economic crisis of 2008-09 and preventing it from becoming a full-blown depression. This book assesses the progress of the G20 with a focus on India. It discusses the role India has played in the success of the G20 process and, more importantly, delineates the possible barriers to India's enhanced involvement in the G20, and in global governance in general. As the global economy remains mired in uncertainties - stemming from the Euro crisis, lacklustre economic performance in the United States, and slowing of major emerging economies - this volume fills the need for a collection of analytical research papers from the perspective of emerging economies, and takes stock of the performance of the G20 thus far. It also points towards the unresolved issues and the future course of action in global financial and macroeconomic stance.
The G20: evolution, functioning and prospects, a concise review / Parthasarathi Shome -- Seciton 2: Financial sector reforms and regulation. Financial regulation and the G20: options for India / Ashima Goyal -- Financial sector reforms under the G20 and the Indian banks / Poonam Gupta -- Section 3: Global macroeconomic coordination and reforming international financial institutions. The G20MAP, sustaining global economic growth and global impalances: India's role in supporting cooperation among global macroeconomic policymakers / David Vines -- Reform of international financial institutions / T.N. Srinivasan -- Capital controls: instruments and effectiveness / Parthasarathi Shome, Jyotirmoy Bhattacharya, Shuheb Kahn -- The international monetary system: mitigating risks from dominance of the dollar and India's stance / Renu Kohli -- Challenges in IMS reforms: emerging markets' perspective / Alok Sheel -- The Chiang Mai initiative and its relevance for India / Sheetal K. Chand.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: International economic relations; International finance; Economic policy; Economic development -- India; Economic development -- Developing countries; Group of Twenty countries; India -- Foreign economic relations